RIGHT VENTRICULAR FUNCTIONAL CHARACTERISTICS IN HEART FAILURE PATIENTS USING ECHOCARDIOGRAPHY AT THE DEPARTMENT OF CARDIOLOGY, BAI CHAY HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the correlation between right ventricular (RV) function on echocardiography and the clinical and paraclinical characteristics of patients with heart failure.Patients and Methods: A descriptive study was conducted on the clinical, paraclinical, and RV echocardiographic characteristics of 60 patients with heart failure. The study was carried out at the Cardiology Department, Bai Chay Hospital, in 2025. Evaluated echocardiographic parameters included: Tricuspid annular plane systolic excursion (TAPSE); Fractional area change (FAC); Systolic excursion velocity (S’); Right ventricular index of myocardial performance (RIMP); tricuspid E wave; tricuspid A wave; and tricuspid e’ wave.Results: The prevalence of TAPSE < 17mm was 65.0%, followed by S’ < 9.5cm/s at 60.0%, while RIMP > 0.54 accounted for the lowest proportion at 23.3%. The RV E/e’ ratio was significantly higher in males than in females (p < 0.05). Mean values of TAPSE, FAC, and S’ in the group with EF≤ 40 were lower than those in the 40-50% and EF ≥50 groups (p < 0.05). Mean TAPSE, S’, and FAC indices were also lower in the group with left ventricular diastolic dysfunction compared to the group without (p < 0.05). There was weak negative correlations between the left atrial volume index and TAPSE (r = -0.294, p < 0.05), FAC (r = -0.287, p < 0.05).Conclusion: The TAPSE, S’, and FAC indices serve as effective indicators for identifying right ventricular impairment, with TAPSE and FAC showing a weak inverse correlation with left atrial volume.
Keywords: Right ventricular function, heart failure, echocardiography.